BALANCING RISK AND INCENTIVES: INTEGRATING MRG INTO FIXED PAYMENT MECHANISMS ON HOSPITAL PPP STRUCTURES - Abdul Fatah, Anton; Iqbal, Roihans Muhammad (Faculty of Economics and Business University of Mataram, 2024)
The success of a Public-Private Partnership (PPP) project relies on the appropriate risk allocation from the government to the private sector. The government employs mechanisms such as Minimum Revenue Guarantees(MRGs) within PPP project schemes. Research on MRGs, however, remains very limited in the Indonesian context. Therefore, this conceptual study proposes the adoption of minimum revenue guarantees into fixed payment mechanisms in PPP projects within the hospital sector and explores how to integrate several principles of minimum revenue guarantees into a fixed payment structure. This conceptual study employs a literature review approach, examining various studies and existing implementations, and synthesizing them for adoption in the Indonesian context. The conceptual study finds that the principles of minimum revenue guarantees can be adapted to fixed payment schemes in PPP projects for the hospital sector, and private entities can optimize their revenue from certain services.